Persistent long-term platelet activation and endothelial perturbation in women with Takotsubo syndrome - Amadio, Patrizia; Porro, Benedetta; Cavalca, Viviana; Barbieri, Silvia Stella; Eligini, Sonia; Fiorelli, Susanna; Di Minno, Alessandro; Gorini, Alessandra; Giuliani, Mattia; Werba, Josè Pablo; Cosentino, Nicola; Olivares, Paolo; et al. (Biomedicine & pharmacotherapy, 2021)
[Display omitted] •Persistent greater amount of adrenaline was found in TTS during long-term follow-up.•TTS show endothelial perturbation with low citrulline and high thrombomodulin levels.•TTS display residual TXA2 production even though low dose ASA treatment.•Increased TXA2 production is paralleled by enhanced platelet aggregation. Takotsubo (TTS) syndrome is an acute cardiac condition characterized by transient and reversible left ventricle dysfunction that mainly affects postmenopausal women. Catecholamine burst is the most accredited mechanism underpinning TTS onset and leading to endothelial dysfunction and platelet activation. Even if the use of low dose acetylsalycilic acid (ASA) in this clinical setting is based on both clinical presentation and unfavorable long-term prognosis, its efficacy has been recently challenged. This study was designed to assess endothelial function, residual thromboxane formation and platelet aggregation in TTS women on low-dose ASA treatment at long-term follow-up. Twenty-eight females with previously diagnosis of TTS syndrome were enrolled. Data were compared to those obtained from 23 coronary artery disease (CAD) women with a history of acute myocardial infarction, and 26 control subjects with no TTS or clinically evident CAD. Psychological and clinical profile were assessed in all study groups at the enrollment. Main metabolites involved in L-arginine/nitric oxide pathway, urinary prostacyclin, serum and urine thromboxane metabolites were measured by LCMS/MS methods. Thrombomodulin levels were quantified using an ELISA kit, and platelet aggregation, carried out on platelet rich-plasma, was induced by ADP or by epinephrine (EPI), norepinephrine (NORE) and TRAP-6, alone or in association with ADP and evaluated by Born’s method. In TTS women an endothelial derangement, characterized by reduced citrulline production and increased thrombomodulin concentration, with no perturbation in prostacyclin levels, was evidenced. In addition, despite ASA treatment, TTS displayed a higher residual thromboxane formation, in parallel with an enhanced platelet response to compared to CAD. Our study highlighted the presence of endothelial perturbation in TTS patients even at long-term from the index event. The residual thromboxane production and platelet aggregation still leave open the question about the use of low dose ASA in this clinical setting.